2003
DOI: 10.1001/archinte.163.15.1849
|View full text |Cite
|
Sign up to set email alerts
|

Argatroban Anticoagulation in Patients With Heparin-Induced Thrombocytopenia

Abstract: Argatroban therapy, compared with historical control, improves outcomes, particularly new thrombosis and death due to thrombosis, in patients with heparin-induced thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
457
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(482 citation statements)
references
References 26 publications
(55 reference statements)
19
457
0
6
Order By: Relevance
“…The argatroban approval trials 55,56 performed in the 1990s enrolled patients on the basis of clinical suspicion of HIT alone (without requirement for a positive test for HIT antibodies), and although the frequency of antibody-positive status was reported to be only 57% in 1 of the studies, 55 the thrombotic event rate has not (to the best of our knowledge) been reported for the subgroup of patients likely to have had HIT on the basis of serologic detection of HIT antibodies. The aforementioned study by Kang et al 5 reported a thrombotic rate of 25% for patients treated with either danaparoid or argatroban but did not specify which patients with laboratory-confirmed HIT were treated with argatroban.…”
Section: Discussionmentioning
confidence: 99%
“…The argatroban approval trials 55,56 performed in the 1990s enrolled patients on the basis of clinical suspicion of HIT alone (without requirement for a positive test for HIT antibodies), and although the frequency of antibody-positive status was reported to be only 57% in 1 of the studies, 55 the thrombotic event rate has not (to the best of our knowledge) been reported for the subgroup of patients likely to have had HIT on the basis of serologic detection of HIT antibodies. The aforementioned study by Kang et al 5 reported a thrombotic rate of 25% for patients treated with either danaparoid or argatroban but did not specify which patients with laboratory-confirmed HIT were treated with argatroban.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with historical controls, argatroban was associated with reduced thrombotic events (relative risk reduction, 0.44 to 0.62). 4,16 The starting dose should be reduced by 75% in a patient with significant liver dysfunction because argatroban undergoes hepatobiliary excretion. Prolongation of the INR by argatroban is considerably greater than that observed with lepirudin, 17 which complicates argatrobanwarfarin overlap; this underscores the importance of postponing warfarin pending substantial resolution of HIT (to avoid warfarin-induced microvascular thrombosis).…”
Section: Argatrobanmentioning
confidence: 99%
“…6 However, the end points of death and amputation did not differ significantly between argatroban-treated patients and historical controls. 4,5 Furthermore, major bleeding rates did not differ between these 2 groups.…”
Section: Introductionmentioning
confidence: 82%
“…24 Major bleeding was defined as retroperitoneal or intracranial bleeding, bleeding into a prosthetic joint, decrease in hemoglobin of 20 g/L or more, and/or clinically evident bleeding requiring transfusion of 2 units or more of packed red blood cells. 4,5 All other bleeding was considered minor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation